PENGGUNAAN METODE LIFE CYCLE COST ANALYSIS (LCCA) UNTUK PENGHITUNGAN EFISIENSI ENERGI PADA GEDUNG DEPO PENYIMPAN ARSIP DI LEMBAGA ARSIP NASIONAL REPUBLIK INDONESIA - , Wulan Diah Puspitowati, Dr. Ir. Adi Djoko Guritno, MSIE. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Arsip Nasional Republik Indonesia (ANRI) or National Archives of the Republic of Indonesia is the archival institution that has a responsibility in the organization of archives, including the national static archives. These archives should be stored in a specific conditioned space and buildings in order that the preservation can be maintained. Construction of the archive repository building is distinguished structurally, architecturally and in mechanical and electrical, with MVAC system (Mechanical Ventilation and Air Conditioning) being the largest cost component in the building. This condition is due to the MVAC system being operated 24 hours a day in every day, non-stop, to be able to achieve its function in preserving the archives. The high operational cost requires that the archives repository building at ANRI be retrofitted